A New All-Optical Signal Regeneration Technique for 10 GB/S DPSK Transmission System - Bhagwan Das; Mohammad Faiz Liew Abdullah; Nor Shahida Mohd Shah (Institute of Advanced Engineering and Science, 2016)
The transmission of high power inside the optical fiber, produce amplitude noise, phase noise and other transmission impairments that degrade the performance of optical communication system. The signal regeneration techniques are used to mitigate these nonlinear impairments in the electrical or in the optical domain. All-optical signal regeneration techniques are one of the solutions to mitigate these nonlinear transmission impairments in the optical domain without converting the signal from optical to electrical domain. The existing techniques are not capable enough to attain the Bit Error Rate (BER) less than 10-10 with the power penalty less than – 9dBm. In this paper, a new all-optical signal regeneration technique is developed that mitigate amplitude and phase noises in the optical domain. The new optical signal regeneration technique is developed by combining the two existing technique one is 3R (Reshaping, Reamplification and Retiming) regeneration and other is Phase Sensitive Amplification (PSA). The 10Gb/s Differential Phase shift Keying (DPSK) noisy transmission system is used to verify the features of developed technique. The developed technique successfully mitigates the nonlinear impairments from the noisy DPSK system with significant improvement in BER at low power penalty with the additional feature of high Q-factor and an eye open response for the regenerated signal. It is determined that BER of 10-12 is achieved at the power penalty of -14 dBm with Q-factor of 42 and an eye opened response. The developed technique in the DPSK system is realized using commercial software package Optisystem. The designed technique will be helpful to enhance the performance existing high-speed optical communication by achieving the minimum BER at low power penalty.